Predicting the effect of climate change on the distribution of Philippine native honey bees - Alambra, Sarah Frances S.; Flores, Mary Joyce L. (Cebu City, Cebu Department of Biology and Environmental Science, College of Science, University of the Philippines Cebu, 2023)
Bees act as essential pollinators and prey in ecosystems as well as producers of food and medicine. Numerous studies worldwide have found that the suitability ranges of bee species in their respective areas are expected to change due to climate change. Yet, studies predicting the effect of climate change on the distribution of native bees in the Philippines are lacking. To address this, species distribution models (SDMs) were constructed using Maximum Entropy (MaxEnt) to predict the potential distribution of Apis cerana and Apis dorsata under current and future climate conditions as projected in Representative Concentration Pathway scenarios (RCP 4.5 and RCP 8.5) for the years 2040 and 2070 under the global circulation model CNRM-CM5. Occurrence records and bioclimatic variables were used to develop the models. A 10-fold cross-validation scheme was used to evaluate model performance alongside the area under the curve (AUC) statistic to determine model accuracy. The current and future distributions of two forage flowering plants, Mangifera indica L. and Mimosa podia were also modeled to determine the effect of their distributions on the study species. AUC values of the four models ranged between 0.70-0.80, indicating moderate performance. Habitat suitability for both honey bee species were predicted to increase by 2070 at RCP 8.5. A number of overlaps were maintained between the projected current and future honey bee and flowering plant distributions. The finding of this study could aid in the development of appropriate conservation strategies for the protection of these native honey bees. It could also fill the knowledge gap on the global effects of climate change on bees under the Philippine setting and encourage further study on other species of Philippine native bees.
Thesis (Bachelor of Science in Biology)--University of the Philippines Cebu. June 2023.